The local feeling in three southern cities - Romero, Emilio (1996)
When glossing the life of these cities there is another suggestive topic of interest: the moment in which the idea of ​​the homeland was born. But before this idea germinated, a feeling preceded that is worthy of study, because it was a characteristic feeling of these cities and of which there are suggestive examples in urban chronicles. Such a feeling is localism, from which the first national feeling was born. After the first years of the conquest, a new patriotism was born, a new sentiment.